PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KURSUS KOMPUTER DALAM KERANGKA TEORI JIM IFE (STUDI KASUS DI PUSAT KEGIATAN BELAJAR MASYARAKAT BINTANG FLOBAMORA KOTA KUPANG) - Salan, Patrisius; Syukur, Abdul; Makleat, Nirwaning (Education For All, 2023)
Community empowerment is an effort to increase the dignity of the community so that they are able to escape the shackles of poverty. According to the theory of community empowerment put forward by Jim Ife, empowerment can be said to have run optimally when the four perspectives, namely the pluralist perspective, elitist perspective, structuralist perspective, and post-structuralist perspective, are applied simultaneously. The purpose of this study was to determine the application of the four perspectives proposed by Jim Ife in the theory of community empowerment at PKBM Bintang Flobamora. This research method uses qualitative methods with a case study approach. The research location is PKBM Bintang Flobamora, Kupang City. The subjects in this study were the heads and staff of PKBM Bintang Flobamora, instructors and learning residents of PKBM Bintang Flobamora. Collecting data using interview techniques, observation, and documentation studies. Data analysis techniques in the form of data collection, data reduction, data presentation, and drawing conclusions. The triangulation used to explain the validity of the data is source triangulation and technique triangulation. The results of the study show that PKBM Bintang Flobamora has implemented the four empowerment perspectives. From a pluralist perspective, services such as computer course training have been provided, then from an elitist perspective, PKBM Bintang Flobamora has collaborated with various parties such as the education office, religious institutions, and also government agencies. Then, from a structuralist perspective, PKBM Bintang Flobamora has generalized all services for every learning citizen. And the post-structuralist perspective of PKBM Bintang Flobamora does not only focus on computer course training, but also provides other guidance.